Navigating Financial Decision-Making: A Phenomenological Study of Women Entrepreneurs and Cultural Norms in Bugis-Makassar Communities - Amin, Andi Mustika (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study investigates how women entrepreneurs in Bugis–Makassar communities interpret and enact financial decision-making within a cultural landscape shaped by siri’ (honor), sipakatau (mutual respect), and dense kinship networks. Using a phenomenological approach based on in-depth interviews, observations, and field interactions in South Sulawesi, the research uncovers how financial choices are negotiated through culturally embedded logics rather than individual rationality alone. Findings reveal five interconnected patterns: negotiated autonomy, honor-driven financial governance, family-based financial intermediation, cautious innovation, and digitally mediated boundary management. These themes illustrate that women navigate financial decisions by balancing business imperatives with moral expectations, reputational considerations, and relational obligations. The study argues that entrepreneurial finance in this context is relational, moral, and affective, challenging mainstream assumptions about individualistic financial autonomy. The analysis contributes to ongoing debates on women’s entrepreneurship by demonstrating that empowerment must be understood as a negotiated, culturally situated process rather than unilateral resource control. Policy implications include the need for culturally attuned financial programs, small matching grants, digital capability support, and engagement with household decision-makers. The study underscores the importance of aligning financial inclusion initiatives with local value systems to reduce reputational risk and enhance women’s economic agency. It further calls for mixed-methods research to bridge phenomenological insights with scalable measures of norms. Overall, the findings highlight that economic behavior among Bugis–Makassar women is inseparable from identity, reputation, kinship, and evolving digital practices, offering a nuanced lens for designing more effective entrepreneurship and financial inclusion interventions.